Tinjauan Hukum Terhadap Perbuatan Melawan Hukum Atas Penguasaan Sebidang Tanah Yang Telah Mencapai Daluwarsa Menurut Kitab Undang-Undang Hukum Perdata: (Studi Putusan Perkara Nomor. 19/Pdt.G/2019/PN.KRS) - Abdur Rohim; As’ad Romadhoni (JUSTNESS - Jurnal Hukun dan Agama, 2021)
An unlawful act is an act that causes harm to another person, and requires the person who caused the loss to compensate for the loss. The fact shows that almost all cases related to land are an act against the law, namely by controlling land belonging to other people without rights. The control or ownership of a plot of land can be done in several ways, one of which is by expiry (past time).The problems studied in this research and its objectives are first to find out, examine, and analyze the provisions or legal rules governing unlawful acts over the control of a plot of land that has reached expiration according to the provisions of the Civil Code, Second to find out, examine and analyze the legal considerations of the decision. Kraksaan District Court case no. 19/Pdt.G/2019/PN.Krs.Based on the formulation of the problem and research objectives, the type of research used is juridical-normatl by using the statute approach and case approach.The results of the research in the preparation of this thesis, firstly Acts against the Law (PMH) are regulated in Article 1365 to Article 1380 of the Civil Code, Land Control / Property Rights are regulated in Article 20 paragraph 1 of Law no. 5 of 1960 Jo. Article 32 paragraph 1 of PP Number 24 of 1997 and Expiration are regulated in Article 1946-1993 of the Civil Code, the two decisions of the Judges of the Kraksaan District Court with Case Number 19/Pdt.G/2019/P N.Krs have been through appropriate legal considerations based on the facts of the trial . Keyword: Unlawful Acts, Land Tenure, Daluwama